Portable Low-Cost CT Scanner Prototype Based on Coincidence Measurements - M. S. Hamideen (Jordan Journal of Physics, 2025)
A prototype design of Computed Tomography scanner has been tested. The major system employs a gamma ray source, scintillation detectors, a data logger and a three-dimensional sample position controller. The image resolution is determined by the step size and the diameter of the gamma ray beam which is controlled by the pinhole collimator. This device is being designed as a prototype gamma ray scanner with modifications in the type of radiation being used, electronics setup and the rotation and translation techniques. In this scanner, however, the object is rotated instead of the entire detector-radiator system. The type of radiation being used will not be an x-ray tube, but will be an indirect byproduct of Na-22+β- decay. This source emits positrons at the surface of the object which rapidly annihilate with atomic electrons that result in the emission of 2 back-to back 511 keV annihilation photons that can be used to electronically require coincidence between gamma detections and therefore reduce background radiation being detected. It is obvious that tomographic imaging is a complex procedure, thus, the main motivation of the work is to prove the capabilities and performances of a prototype CT scanner based on coincidence measurements, as an imaging system. Keywords: Coincidence Measurements; CT scanner, Prototype Design; Annihilation Photons. PACS: 81.70.Tx.